2021
DOI: 10.1016/j.micpath.2021.105040
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of molecular mechanisms in β-lactam resistant gram-negative bacteria

Abstract: Antibiotic-resistant bacteria are considered one of the major global threats to human and animal health. The most harmful of the resistant bacteria are β-lactamases producing Gram-negative species (β-lactamases). β-lactamases constitute a paradigm shift in the evolution of antibiotic resistance. Therefore, it is imperative to present a comprehensive review of the mechanisms responsible for the development of antimicrobial resistance. Resistance due to β-lactamases develops through to a variety of mechanisms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 102 publications
0
21
0
3
Order By: Relevance
“…through horizontal gene transfer [ 50 ]. After mobilization of this gene from the chromosome into a plasmid, mutations lead to further diversification and provide the opportunity for expansion of hydrolytic activity to other extended-spectrum cephalosporins such as ceftazidime [ 51 ]. In animals, the CTX-M enzyme was first identified in 1988 from E. coli isolated from dogs’ feces in Japan [ 52 ].…”
Section: Mechanisms Of Resistance To Beta-lactam Antibioticsmentioning
confidence: 99%
“…through horizontal gene transfer [ 50 ]. After mobilization of this gene from the chromosome into a plasmid, mutations lead to further diversification and provide the opportunity for expansion of hydrolytic activity to other extended-spectrum cephalosporins such as ceftazidime [ 51 ]. In animals, the CTX-M enzyme was first identified in 1988 from E. coli isolated from dogs’ feces in Japan [ 52 ].…”
Section: Mechanisms Of Resistance To Beta-lactam Antibioticsmentioning
confidence: 99%
“…Generally, all beta-lactamase variants are classified into four classes, A (serine penicillinases), B (metallo-beta-lactamases), C (cephalosporinases) and D (oxacillinases), which give resistance to penicillins, most β-lactams, cephalosporins and cloxacillin, respectively [ 11 ]. Some key families of ESBL-encoding genes, such as bla CTX-M , bla TEM and bla SHV are grouped in class A [ 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other ESBL genes include bla OXA , bla VEB , bla VER and bla GES [ 7 , 8 , 13 ]. The co-presence of ESBL genes in the same species is a significant threat of transfer to other species [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3: Antibiotic Susceptibility test for Proteus mirabilis to 14 Antibiotics Salama et al, (2021) and the Iraqi study of Hussain, (2016) revealed that P.mirabilis recovered from different clinical specimens are characterized by multidrug resistant. According to Hussain et al,(2021), bacterial isolates can develop chromosomally β-lactamase enzyme, which hydrolyzes chemical compounds containing a β -lactam ring, causing resistance to β -lactam antibiotics. In the same way, horizontal gene transfer (HGT) is vital in -lactam resistance.…”
Section: Antibiotics Susceptibility Test Of Proteus Mirabilismentioning
confidence: 99%